2007
DOI: 10.1002/acp.1386
|View full text |Cite
|
Sign up to set email alerts
|

The intensity of recent and distant life regrets: an integrated model and a large scale survey

Abstract: The research considers three predictors of the intensity of life regrets: (a) whether the regretted behaviour is an action or a failure to act, (b) the severity of its consequences and (c) the extent to which the behaviour was justified. It is hypothesised that the intensity of recent and distant regrets will be predicted by different combinations of these predictors. Regression analyses on regrets reported by 957 French adults support this hypothesis. The intensity of recent regrets is predicted by the conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Firstly, we found no evidence to support the assertion of Gilovich and Medvec (1995, p. 381) that “when people look back on their lives, it seems to be their regrettable failures to act [inactions] that stand out and cause greater grief.” Rather, the effect of action/inaction was small, and it was actions that were associated with greater regret intensity. Furthermore, in line with previous studies (Feldman et al, 1999; Bonnefon and Zhang, 2008) we found no evidence to support the hypothesis that the passing of time leads to an increase in regret intensity for inactions and a converse reduction in intensity for actions.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Firstly, we found no evidence to support the assertion of Gilovich and Medvec (1995, p. 381) that “when people look back on their lives, it seems to be their regrettable failures to act [inactions] that stand out and cause greater grief.” Rather, the effect of action/inaction was small, and it was actions that were associated with greater regret intensity. Furthermore, in line with previous studies (Feldman et al, 1999; Bonnefon and Zhang, 2008) we found no evidence to support the hypothesis that the passing of time leads to an increase in regret intensity for inactions and a converse reduction in intensity for actions.…”
Section: Discussionsupporting
confidence: 75%
“…Emotional frequency and intensity are distinct processes underlying the experience of affect (Diener et al, 1985; Schimmack and Diener, 1997) and they are not necessarily highly correlated: Frequent emotions (e.g., happiness) may not necessarily be intense, while infrequent emotions (e.g., rage) may be very intense. Studies assessing regret frequency as a proxy for regret intensity are therefore potentially misleading, and this may explain why the few studies directly distinguishing regret frequency and intensity found inaction regrets to be more frequently reported but no more intense than action regrets (Feldman et al, 1999; Bonnefon and Zhang, 2008). This study will therefore focus on reported regret intensity (rather than frequency) in order to provide conclusions as to the key drivers of regret intensity across the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated in the general population (Feeney et al, 2005;Feldman, Miyamoto & Loftus, 1999), among the intellectually gifted (Hattiangadi et al, 1995), and in several cultures (Bonnefon, & Zhang, 2008;Gilovich et al, 2003;Jokissari, 2003;Timmer et al, 2005).…”
Section: Agency and Autobiographical Regretsmentioning
confidence: 98%
“…France (Bonnefon & Zhang, 2008), Finland (Jokisaari, 2003;2004), Germany (Timmer, Westerhof & Dietmann-Kohli, 2005;Wrosch & Heckhausen, 2002) and the U.K. (Feeney, Gardiner, Johnston, Jones & McElvoy, 2005). So although it is impossible to say categorically that regret is universal, most regret researchers assume it to be so.…”
Section: Who Experiences Regret What Do People Regret and Why?mentioning
confidence: 99%
“…This recruitment procedure was introduced inBonnefon and Villejoubert (2006), and has been applied since to a rich variety of psychological issues, including investigations of collective judgement(Bonnefon, 2007), life regrets(Bonnefon & Zhang, 2008), and comparative happiness.…”
mentioning
confidence: 99%